(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
On September 1-8, 1920, the First Congress of the Peoples of the East was held in Baku, the capital of Azerbaijan. The purpose of establishing Congress was to spread the ideas of socialism to Muslim countries. For this purpose, many delegates from Turkestan were sent to participate in the session. In the article, the issues of coverage of the Conference of Eastern Nations in the historiography of Uzbekistan are analyzed on the basis of primary sources.